Influence of Skewed-slot Stator on the Bearing of Permanent Magnet Motor - HE Siyuan; FU Minli; YANG Jinxia (Kongzhi Yu Xinxi Jishu)
As an effective method to reduce cogging torque, skewed-slot stator has been widely adopted in the design of permanent magnet motor. However, skewed slot would produce axial force which may affect the life of bearing. This paper theoretically analyzes the effect of skewed-slot stator on the bearing force and proposes a method that the bearing structure is reasonably designed to decrease the effect of skewed slots on the bearing life. Validity and availability of the method are verified by the results of real running example motors.